Dashboard Para La Identificación De Los Posibles Intentos De Fraude De Las Prestadoras De Servicio Asociadas A Las Entidades Aseguradoras - Alfaro Prieto, Carlos Alberto (Universidad Antonio Nariño, 2023)
Fraud currently negatively affects health insurance companies, for this reason an early detection must be made by auditors, and based on the findings, decisions must be made to improve the detection of fraudulent cases. But this activity every day generates greater challenges in the audit area as more and more cases of fraud to be reviewed which can be from fraudulent billing and coding, falsification of documents, submission of fraudulent claims and misuse of the patient's identity This project provides an automated tool to detect and prevent fraud in healthcare services.